Deep blue : a contemplation evoked “8 x 8” - Neo, Yong Qin (2015)
Welcome to the world of Chess and get ready to be constrained by your own biological straitjacket. “8x8”, as the set of prototypes are named; is the brainchild forged out of deep contemplation from the unprecedented defeat of Gary Kasparov, then reigning world chess champion, against International Business Machines Corporation (IBM)’s Deep Blue. 8x8 attempts to take on 1,500 years old of what started off as mankind’s brilliance, to an eventual realization of obsolete and stagnation on May 11, 1997. For the first time, both traditional chess enthusiast and even technophiles alike are thrown into frenzy. Are we about to build a whole new generation of machines that will soon render us towards extinction? Investigations will be made through unveiling the Artificial Intelligence (AI)’s cloak of invincibility, to unlocking the mechanism behind as to what made this antiquated game ticked, and its intertwined relationships to our societies and culture. Attempts made for its revival comprises of the 3Ds (Dynamics, Design (aesthetics), Deceit). All of which are strategically introduced in order to induce the element of luck and charm into the game play, thereby shifting back the balance and rendering an AI a less attractive opponent. Eighteen years have passed since. Humanity has yet to mount any noteworthy responses to reinstate our lost title of 1,500 years, and was contented leaving it to oblivious. But now the stage is set, you be the judge.